Implementasi Kebijakan Perlindungan Pekerja Migran Indonesia Di Kabupaten Bojonegoro Tahun 2022 : (Studi Kasus di Dinas Perindustrian dan Tenaga Kerja Kabupaten Bojonegoro) - Rupiarsieh; Musta’ana (Prodi Sosiologi Agama, 2023)
Indonesian Migrant Workers (PMI) who work abroad often receive bad treatment such as violence and neglect, both during pre-deployment and during placement. With the emergence of various problems regarding the protection of Indonesian Migrant Workers (PMI), in 2017 the government issued Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. This Law explains that there are three forms of protection for prospective Indonesian Migrant Workers (PMI) or Indonesian Migrant Workers, namely Protection before work, Protection during work, and Protection after work. This research was carried out in order to measure and assess the success of implementing the Indonesian Migrant Worker protection policy at the Bojonegoro Industry and Manpower Service. The problem formulation drawn from the background is how to implement the Indonesian Migrant Worker protection policy in Bojonegoro Regency. This research uses George C. Edward III's theory which focuses on four indicators, namely Communication, Resources, Disposition and Bureaucratic Structure. The research method used is a descriptive research method with a qualitative approach, and the technique for determining informants uses a purposive sampling technique. To collect data, the author used interview, observation and documentation techniques. The results of this research show that based on George C. Edward III's theory, the protection policy for Indonesian Migrant Workers in Bojonegoro Regency has not been implemented as it should be. Protection before work, during work, and after work or after work has not been implemented at the Bojonegoro Industry and Manpower Service. This is proven by the existence of several deviations from communication factors and funding source factors which make the implementation of the Indonesian Migrant Worker Protection policy carried out by the Bojonegoro Regency Industry and Manpower Service unable to run well.